Echinoderm Microtubule Associated Protein Like 1 Is Indispensable for Oocyte Spindle Assembly and Meiotic Progression in Mice - Yin, Hong; Zhang, Teng; Wang, Hao; Hu, Xin; Hou, Xuan; Fang, Xianbao; Yin, Yaoxue; Li, Hui; Shi, Lanying; Su, You-Qiang (Frontiers in Cell and Developmental Biology, 2021)
Completion of the first meiosis is an essential prerequisite for producing a functionally normal egg for fertilization and embryogenesis, but the precise mechanisms governing oocyte meiotic progression remains largely unclear. Here, we report that echinoderm microtubule-associated protein (EMAP)-like 1(EML1), a member of the conserved EMAP family proteins, plays a crucial role in the control of oocyte meiotic progression in the mouse. Female mice carrying an ENU-induced nonsense mutation (c.1956T > A; p.Tyr652*) of Eml1 are infertile, and the majority of their ovulated oocytes contain abnormal spindles and misaligned chromosomes. In accordance with the mutant oocyte phenotype, we find that EML1 is colocalized with spindle microtubules during the process of normal oocyte meiotic maturation, and knockdown (KD) of EML1 by specific morpholinos in the fully-grown oocytes (FGOs) disrupts the integrity of spindles, and delays meiotic progression. Moreover, EML1-KD oocytes fail to progress to metaphase II (MII) stage after extrusion of the first polar body, but enter into interphase and form a pronucleus containing decondensed chromatins. Further analysis shows that EML1-KD impairs the recruitment of γ-tubulin and pericentrin to the spindle poles, as well as the attachment of kinetochores to microtubules and the proper inactivation of spindle assembly checkpoint at metaphase I (MI). The loss of EML1 also compromises the activation of maturation promoting factor around the time of oocyte resumption and completion of the first meiosis, which, when corrected by WEE1/2 inhibitor PD166285, efficiently rescues the phenotype of oocyte delay of meiotic resumption and inability of reaching MII. Through IP- mass spectrometry analysis, we identified that EML1 interacts with nuclear distribution gene C (NUDC), a critical mitotic regulator in somatic cells, and EML1-KD disrupts the specific localization of NUDC at oocyte spindles. Taken together, these data suggest that EML1 regulates acentrosomal spindle formation and the progression of meiosis to MII in mammalian oocytes, which is likely mediated by distinct mechanisms.